2021
DOI: 10.3390/su13063226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Performance Work Systems (HPWS) on Hospitality Employees’ Outcomes through Their Organizational Commitment, Motivation, and Job Satisfaction

Abstract: The purpose of this research is to examine the underlying mechanisms inside the so-called black box that relate high performance work systems (HPWS) with employees’ well-being and job performance in hospitality. We surveyed a sample of 494 hotel workers to test a research model that related the following variables: HPWS, organizational commitment, motivation, job satisfaction, quality of life (QoL), and individual job performance. Structural equation modelling, namely through PLS-SEM, was conducted. We confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 90 publications
5
43
1
6
Order By: Relevance
“…OC and motivation are good predictors of satisfaction and quality of work life [49]. Among the factors concerning organizational performance discussed in previous studies is OC [31].…”
Section: The Relationship Between Intrinsic Motivation and Ocmentioning
confidence: 93%
“…OC and motivation are good predictors of satisfaction and quality of work life [49]. Among the factors concerning organizational performance discussed in previous studies is OC [31].…”
Section: The Relationship Between Intrinsic Motivation and Ocmentioning
confidence: 93%
“…Much research has been devoted to job satisfaction. Dorta-Afonso et al [1] in their study revealed that workers' motivation and organizational commitment positively influence job satisfaction, which, in turn, enhances workers' quality of life. Moreover, they found that job satisfaction and quality of life significantly predicted individual job performance.…”
Section: Job Satisfactionmentioning
confidence: 95%
“…Many recent studies confirmed this argument. Dorta-Alfonso et al [1] revealed the relationship between job satisfaction and individual job performance, since satisfied employees will put discretionary effort into their tasks to perform well. While some studies proposed direct relationship between job satisfaction and organizational performance (see [2]), research findings also suggested that the relationship between employee satisfaction and financial performance was mediated by some other variables, such as customer satisfaction [3,4] and organizational commitment [5], highlighting the importance of job satisfaction for organizational success in broader context.…”
Section: Introductionmentioning
confidence: 99%
“…A topic in research is the relationship between a high-performance work system (HPWS, involving three concepts: performance, work practices, and systemic effects [26]) and job satisfaction, with literature data finding a positive and significant correlation between them [27][28][29]. The HPWS implementation creates an environment that provides the employees a higher involvement, participation in decision making, motivation, desire to improve knowledge, skills, and responsibility, with an increase in job satisfaction and ensuring a competitive advantage to the company.…”
Section: Literature Reviewmentioning
confidence: 99%